Efficiency of Melissa officinalis leaf extract in amelioration of oxidative status and histological changes in male albino rats with induced hypothyroidism - Z. R. Majeed; A. A. Sharhan (Regulatory Mechanisms in Biosystems, 2024)
The study was conducted to demonstrate the role of ethanolic leavf extract from Melissa officinalis in treatment of hypothyroidism disease which was induced by the drug carbimazole. The aim of this study was to investigate the effects of oral administration of M. officinalis on oxidative status and histological changes in rats with induced hypothyroidism. Fifty male rats were divided into five groups, ten for each. Group I was selected as negative control and administered orally with normal saline alone, group II served as positive control and tadministered carbimazole (5 mg/kg) anti-thyroid drug for six weeks to induce hypothyroidism. Group III was administered carbimazole (5 mg/kg) for six weeks to induce hypothyroidism, then treated with plant extract (75 mg/day). Group IV was administered carbimazole (5 mg/kg) for six weeks to induce hypothyroidism, then treated with plant extract (150 mg/day) and group V was administered carbimazole (5 mg/kg) for six weeks to induce hypothyroidism then treated with thyroxin (50 µg). The results showed that there was no significant difference in MDA levels in the third group when compared with groups I, IV and V while the results showed a significant decrease when compared with group II. The results showed no significant differences in the levels of SOD in group III when compared with the groups I, IV and V, while there was a significant increase when compared with group II. The results of the histological study of the thyroid gland in group II showed an irregular shape of the colloids with thickening in the epithelial cells and uneven distribution of the thyroglobulin (some appeared full and others were empty) with slight infiltration of inflammatory cells and thyroid cells apoptosis showed a normal structure of the thyroid gland, while the result demonstrated repair to normal structure in groups III, IV and V, which looked the same as the control group. In the liver section in the II group, hepatocytes were arranged irregularly around the central vein, in addition to the presence of inflammatory material in the central vein, and presence of inflammatory cells, as well as apoptosis in the hepatocytes, while the result showed return to normal structure in the III, IV and V group, which looked the same as the control group. Also the V group showed a slight infiltration on inflammatory cells. On the other hand, the results for group II showed irregular shape of the renal nephrons with severe infiltration of lymphocytes, severe hemorrhage and irregular shape of the renal tubules, while the results for the III, IV and V groups revealed a return to normal structure the same as in the control. In conclusion, M. officinalis leaves extract regulate thyroid levels in rats. It alleviated the inflammatory response by suppressing the MDA and increasing SOD in treatment groups. These results might strengthen the protective effect of M. officinalis extract in a rat model of hypothyroidism.